Step
*
of Lemma
rexp-of-nonneg-stronger
∀x:ℝ. ((r0 ≤ x) 
⇒ ((r1 + x) ≤ e^x))
BY
{ (Auto
   THEN (InstLemma `rexp-is-limit` [⌜x⌝]⋅ THENA Auto)
   THEN Assert ⌜Σi.if (i =z 0) then r1
                if (i =z 1) then x
                else r0
                fi  = r1 + x⌝⋅) }
1
.....assertion..... 
1. x : ℝ
2. r0 ≤ x
3. Σn.(x^n)/(n)! = e^x
⊢ Σi.if (i =z 0) then r1
if (i =z 1) then x
else r0
fi  = r1 + x
2
1. x : ℝ
2. r0 ≤ x
3. Σn.(x^n)/(n)! = e^x
4. Σi.if (i =z 0) then r1
if (i =z 1) then x
else r0
fi  = r1 + x
⊢ (r1 + x) ≤ e^x
Latex:
Latex:
\mforall{}x:\mBbbR{}.  ((r0  \mleq{}  x)  {}\mRightarrow{}  ((r1  +  x)  \mleq{}  e\^{}x))
By
Latex:
(Auto
  THEN  (InstLemma  `rexp-is-limit`  [\mkleeneopen{}x\mkleeneclose{}]\mcdot{}  THENA  Auto)
  THEN  Assert  \mkleeneopen{}\mSigma{}i.if  (i  =\msubz{}  0)  then  r1
                            if  (i  =\msubz{}  1)  then  x
                            else  r0
                            fi    =  r1  +  x\mkleeneclose{}\mcdot{})
Home
Index